Penerapan Metode HIRARC dalam Menganalisis Risiko Bahaya dan Upaya Pengendalian Kecelakaan Kerja di Area Crusher dan Belt Conveyor PT. Semen Padang - Bianda F Aprilla; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Semen Padang is a mining industry closely related to the field activities of its workers. Each type of mining work has potential and hazard factors with various risks that lead to work accidents, especially in the crusher and belt conveyor areas. This study aims to identify the hazard risks, analyze the severity of each hazard risk and its risk category, and apply the HIRARC method in controlling the hazard risks found in the crusher and belt conveyor areas of PT. Semen Padang. This research is a qualitative research with descriptive method using hazard risk analysis in the form of likelihood and consequence, as well as risk matrix analysis and the HIRARC method to determine hazard control. Based on the research results, it can be seen that 12 types of hazard risks were found in the crusher area and 8 hazard risks in the conveyor belt area of PT. Semen Padang from 2018 to 2021 with a hazard severity level of 60% in the medium category, 25% in the high category, and 15% in the low category. The HIRARC method applied in controlling these risks includes: Elimination, Substitution, Engineering, Administration, and PPE.